Understanding the squamous cell carcinoma immune microenvironment - Saeidi, Vahide; Doudican, Nicole; Carucci, John A. (Frontiers in Immunology, 2023)
Primary cutaneous squamous cell carcinoma (cSCC) is the second most common human cancer with a rising incidence of about 1.8million in the United States annually(1). Primary cSCC is usually curable by surgery; however, in some cases, cSCC eventuates in nodal metastasis and death from disease specific death. cSCC results in up to 15,000 deaths each year in the United States(2). Until recently, non-surgical options for treatment of locally advanced or metastatic cSCC were largely ineffective. With the advent of checkpoint inhibitor immunotherapy, including cemiplimab and pembrolizumab, response rates climbed to 50%, representing a vast improvement over chemotherapeutic agents used previously. Herein, we will discuss the immune microenvironment associated with cSCC. We will discuss phenotype and function of SCC associated Langerhans cells, dendritic cells, macrophages, myeloid derived suppressor cells and T cells as well as SCC-associated lymphatics and blood vessels. We will also discuss possible role(s) of SCC-associated cytokines in progression and invasion. We will discuss the SCC immune microenvironment in the context of currently available and pipeline therapeutics.